A rule-aware time-varying conflict risk measure for MASS considering maritime practice. (November 2021) - Li, Mengxia; Mou, Junmin; Chen, Linying; He, Yixiong; Huang, Yamin
Highlights: A practical Rule-aware Time-varying conflict risk (R-TCR) measure incorporating COLREGS and maritime practice is proposed. The ship maneuverability has been taken into account in the construction of R-TCR. The proposed R-TCR can provide the conflict risk encountering with multiple ships, early warning, and tips for evasive actions. The proposed R-TCR has the potential for supporting human-like evasive actions in maritime autonomous surface ships (MASS). Abstract: Conflict detection is a vital step of collision prevention at sea, determining if there is a risk of collision and when to take preventing actions. This article proposes a practical Rule-aware Time-varying Conflict Risk (R-TCR) for ship collision avoidance. Considering maritime practice, the conflict risk measure takes the ship maneuverability, the COLREGs, and good seamanship into account in the conflict risk measure. Specifically, the conflict risk is formulated as a ratio of achievable maneuvers leading to a collision to all achievable maneuvers. Simulations are carried out to show the characteristics of R-TCR. The results show that the R-TCR evaluates the entire conflict risk incorporating COLREG rules, multiple targets, different maneuverability, and varying ship domains. Finally, the proposed measure is applied to analyze the collision accident between two ships. Compared with the conventional risk indicators, the proposed R-TCR can deliver extra information to users, such as providing early warning, showing the room-for-maneuver, and suggesting evasive actions. Besides, the extra information also supports collision avoidance for autonomous ships.